WOMEN'S ENGAGEMENT IN LAW AND DIGITAL TECHNOLOGIES: : AN APPRAISAL - Mokofe, William Manga (International Journal of Law in Changing World, 2025)
The intersection of women, law, and digital technologies is a burgeoning area of study with profound implications for societal structures and individual rights. This paper examines the multifaceted relationship between women, legal systems, and digital technologies, exploring the opportunities and challenges presented by the integration of technology into legal frameworks. It investigates topics such as gender biases in algorithmic decision-making, cybersecurity concerns affecting women, legal responses to online harassment and gender-based violence, women's representation in digital law spaces, and the impact of emerging technologies on women's rights and access to justice. By synthesizing existing research and offering insights into future directions, this paper contributes to a deeper understanding of how digital technologies are reshaping the landscape of law and its impact on women. Furthermore, it underscores the importance of addressing gender disparities and promoting inclusivity in the design and implementation of legal and technological systems. _____ LA PARTICIPACIÓN DE LAS MUJERES EN EL DERECHO Y LAS TECNOLOGÍAS DIGITALES: UNA EVALUACIÓN La intersección entre las mujeres, el derecho y las tecnologías digitales es un área de estudio en auge con profundas implicaciones para las estructuras sociales y los derechos individuales. Este artículo examina la multifacética relación entre las mujeres, los sistemas jurídicos y las tecnologías digitales, explorando las oportunidades y los desafíos que presenta la integración de la tecnología en los marcos legales. Investiga temas como los sesgos de género en la toma de decisiones algorítmica, las preocupaciones sobre ciberseguridad que afectan a las mujeres, las respuestas legales al acoso en línea y la violencia de género, la representación de las mujeres en los espacios jurídicos digitales y el impacto de las tecnologías emergentes en los derechos de las mujeres y el acceso a la justicia. Al sintetizar la investigación existente y ofrecer perspectivas sobre las futuras direcciones, este artículo contribuye a una comprensión más profunda de cómo las tecnologías digitales están transformando el panorama jurídico y su impacto en las mujeres. Además, subraya la importancia de abordar las disparidades de género y promover la inclusión en el diseño e implementación de los sistemas jurídicos y tecnológicos. _____ 女性参与法律与数字技术：评估 女性、法律与数字技术的交叉是一个新兴的研究领域，对社会结构和个人权利有着深远的影响。本文探讨了女性、法律体系和数字技术之间多层面的关系，并探讨了技术融入法律框架所带来的机遇和挑战。研究主题包括算法决策中的性别偏见、影响女性的网络安全问题、针对网络骚扰和性别暴力的法律应对措施、女性在数字法律领域的代表性，以及新兴技术对女性权利和司法公正的影响。通过整合现有研究并展望未来方向，本文有助于更深入地理解数字技术如何重塑法律格局及其对女性的影响。此外，本文还强调了在法律和技术体系的设计和实施中解决性别差异和促进包容性的重要性。